The Relationship Between Knowledge And Attitudes Of Women Of Childbearing Age (WUS) Regarding IUD Contraception With The IUD Contraception Selection Plan (INCH : Journal of Infant and Child Healthcare, 2022)
The low use of the IUD KB is due to the low level of public education. Their knowledge about IUD contraceptives is still lacking, they do not use IUD contraceptives because they do not understand the benefits (effectiveness) of these contraceptives. This study aims to determine the relationship between WUS knowledge and attitudes about IUD contraception with the planned selection of IUD contraception in the Sipayung Health Center Work Area in 2022. The research method used a Cross Sectional design with snowball sampling technique in sampling. The sample of this study amounted to 80 respondents in the Sipayung Health Center Work Area in 2022. Data analysis was univariate and bivariate. The results showed that the majority of WUS knowledge levels were in the poor category (53.8%), WUS attitudes about contraception were negative (60%). The results of the chi square test for knowledge of IUD selection obtained p value of 0.00 and attitude of IUD selection p value of 0.00. The conclusion of this study is that there is a relationship between knowledge and attitudes of women of childbearing age (WUS) about IUD contraception with the IUD contraceptive selection plan